2013
DOI: 10.4187/respcare.02291
|View full text |Cite
|
Sign up to set email alerts
|

Scintigraphic Assessment of Radio-Aerosol Pulmonary Deposition With the Acapella Positive Expiratory Pressure Device and Various Nebulizer Configurations

Abstract: BACKGROUND:The Acapella device produces high-frequency oscillations and positive expiratory pressure to promote bronchial secretion clearance. Its performance during aerosol delivery has not been described. We evaluated the effect of nebulizer and Acapella configuration on pulmonary deposition of radio-tagged aerosol in healthy subjects. METHODS: Ten healthy male subjects (mean age 24.4 ؎ 2.2 y) participated in a crossover study that compared pulmonary delivery of 4 mL of technetium-99m-labeled diethylene tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
(17 reference statements)
1
4
0
1
Order By: Relevance
“…Berlinski also noted that this finding is consistent with the outcome from another laboratory study by Mitchell et al [112], who observed that OPEP devices that avoid restriction of the aerosol pathway (in their case, within the Aerobika* device) do not significantly alter the dose available for inhalation. Looking at evidence from direct measures of drug deposition in the lungs of patients, the large losses of medication in the Acapella*-Up-Draft II Opti-Neb nebulizer arm of the Berlinski study [111] are consistent with the findings from a scintigraphic study with healthy volunteer adults, undertaken by Mesquita et al [110]. This group found that placing a jet nebulizer (ST3, NS, Sa ˜o Paulo, Brazil) distal to an Acapella* Choice OPEP device, as recommended by the manufacturer at that time, substantially decreased intrapulmonary deposition.…”
Section: Opep-nebulizer Therapysupporting
confidence: 64%
See 1 more Smart Citation
“…Berlinski also noted that this finding is consistent with the outcome from another laboratory study by Mitchell et al [112], who observed that OPEP devices that avoid restriction of the aerosol pathway (in their case, within the Aerobika* device) do not significantly alter the dose available for inhalation. Looking at evidence from direct measures of drug deposition in the lungs of patients, the large losses of medication in the Acapella*-Up-Draft II Opti-Neb nebulizer arm of the Berlinski study [111] are consistent with the findings from a scintigraphic study with healthy volunteer adults, undertaken by Mesquita et al [110]. This group found that placing a jet nebulizer (ST3, NS, Sa ˜o Paulo, Brazil) distal to an Acapella* Choice OPEP device, as recommended by the manufacturer at that time, substantially decreased intrapulmonary deposition.…”
Section: Opep-nebulizer Therapysupporting
confidence: 64%
“…However, it is self-evident that airway patency is a necessary precondition before such medications can reach the receptors to provide therapeutic benefits. The combination of inhaled medication delivery with PEP has been established for some time [109,110]. However, recently, with the increased variety of OPEP devices becoming available, there has been increasing interest in exploring the potential for combining OPEP with inhaled medication therapy, delivered principally by a nebulizer [19,110,111].…”
Section: Opep-nebulizer Therapymentioning
confidence: 99%
“…As seen in Table 3, nebulised 99m Tc-DTPA is mainly used to investigate the effect of particular pulmonary delivery equipment, e.g. positive expiratory pressure device, on the aerosol performance of lung deposition [97,[100][101][102][103][104][105]. Other studies with 99m Tc-DTPA focus on distinguishing different lung diseases [74,106,107], understanding the physiology of lung disease [108], and investigating the new application of ventilation scintigraphy [109].…”
Section: Nebulisationmentioning
confidence: 99%
“…Mesquita et al 15 conducted a study to assess lung deposition provided by a variety of nebulizers in combination with the Acapella (Smiths Medical, Watford, United Kingdom) in healthy subjects. The authors hypothesized that placement of the nebulizer distal to the Acapella, as recommended by the manufacturer, would reduce aerosol lung delivery compared with more proximal placement (between the device and mouthpiece) or compared with the nebulizer alone (Fig.…”
Section: Patient Interfacesmentioning
confidence: 99%